2013
DOI: 10.1093/biomet/ast042
|View full text |Cite
|
Sign up to set email alerts
|

Efficient inference for spatial extreme value processes associated to log-Gaussian random functions

Abstract: SUMMARYMax-stable processes arise as the only possible nontrivial limits for maxima of affinely normalized identically distributed stochastic processes, and thus form an important class of models for the extreme values of spatial processes. Until recently, inference for max-stable processes has been restricted to the use of pairwise composite likelihoods, due to intractability of higherdimensional distributions. In this work we consider random fields that are in the domain of attraction of a widely used class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 26 publications
0
111
0
Order By: Relevance
“…Recently, improvements have been obtained for the parameters estimations of some maxstable processes, e.g. Brown-Resnick processes: extremal increments of the process allow to work with a complete likelihood function (Engelke et al, 2015;Wadsworth and Tawn, 2014). A direct modeling of the exceedances of a max-stable process is also possible using a generalized Pareto process (Ferreira and de Haan, 2014) but such an approach is only of interest in the case of asymptotic dependence.…”
Section: Model Inferencementioning
confidence: 99%
“…Recently, improvements have been obtained for the parameters estimations of some maxstable processes, e.g. Brown-Resnick processes: extremal increments of the process allow to work with a complete likelihood function (Engelke et al, 2015;Wadsworth and Tawn, 2014). A direct modeling of the exceedances of a max-stable process is also possible using a generalized Pareto process (Ferreira and de Haan, 2014) but such an approach is only of interest in the case of asymptotic dependence.…”
Section: Model Inferencementioning
confidence: 99%
“…Brown-Resnick processes can be shown to be essentially the only limit of properly rescaled maxima of Gaussian processes (Kabluchko et al 2009) and have been found to yield good fits in applications Jeon and Smith 2012). Their flexibility, and the recent development of efficient inference procedures (Engelke et al 2012;Wadsworth and Tawn 2013), make them particularly attractive. Although Brown-Resnick processes are based on nonstationary Gaussian models, the construction in Eq.…”
Section: Modelsmentioning
confidence: 99%
“…Since the max-stable models are suitable only above some predetermined high threshold, inference is usually made using a censored approach (Huser andJeon and Smith 2012;Thibaud et al 2013). Furthermore, following Stephenson and Tawn (2005), Davison and Gholamrezaee (2012) and Wadsworth and Tawn (2013) show how to incorporate the occurrence times of extreme events, use of which both simplifies the likelihood and allows much more efficient inference in cases of moderate to low spatial dependence.…”
Section: Inferencementioning
confidence: 99%
“…Assuming temporal independence of the y 's, but spatial dependence, the log‐likelihood of the model is written as (λ,κ,b,ψ)=t=1Tlogg(y1t,,yNt), where g is the multivariate density of Brown‐Resnick model. Wadsworth and Tawn () give a closed form expression for g ; however, its computation results in a combinatorial explosion (Castruccio et al, ; Davison & Gholamrezaee, ). It is possible to circumvent this issue by making estimation based on the pairwise log‐likelihood (Padoan et al, ; Varin et al, ) 1(λ,κ,b,ψ)=t=1Ti=1N1j=i+1Nloggij(yit,yjt), where g i j is the bivariate density of ( Y i , Y j ), that is, associated to , and N is the number of stations.…”
Section: Methodsmentioning
confidence: 99%